The Effectiveness of in vitro Somatic Embryogenesis in Eliminating Fanleaf Virus and Leafroll Associated Viruses from Grapevines - Goussard, P.G.; Wiid, J.; Kasdon, G.G.F. (South African Journal of Enology and Viticulture, 2017)
Somatic embryos were successfully regenerated from callus tissue of anthers and ovaries extracted from inflorescences of grapevines infected with grapevine fanleaf virus (GFLV) and grapevine leafroll associated viruses (GLR) respectively. Production of pro-embryogenic masses (PEMS) was controlled by specific growth regulators and culture conditions. Somatic embryos (containing roots and cotyledons) and plantlets were subjected to immunosorbent electron microscopy (ISEM) as well as serological tests (ELISA). Results indicated that somatic embryogenesis derived from ovary tissue of infected grapevines is an effective technique to eliminate grapevine Ieafroll associated viruses from grapevines but the procedure was not successful in the elimination of GFL V from anther source material.